Efficacy and efficacy-influencing factors of stem cell transplantation on patients with Parkinson’s disease: a systematic review and meta-analysis - Zhao, Jianli; Qu, Kang; Jia, Shanshan; Yang, Rong; Cui, Ziting; Li, Jiajia; Yu, Peng; Dong, Ming (Frontiers in Neurology, 2024)
Background: Cell transplants as a treatment for Parkinson's disease have been studied for decades, and stem cells may be the most promising cell sources for this treatment. We aimed to investigate whether stem cell transplantation contributes to the cure for Parkinson's disease and the factors that may influence the efficacy for this therapy. Methods: PubMed, Embase, Cochrane Library, Web of Science, SinoMed, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), and ChinaInfo were thoroughly searched to find controlled trials or randomized controlled trials performing stem cell transplantation in patients with Parkinson's disease. The pooled effects were analyzed to evaluate the weighted mean difference (WMD) with 95% confidence intervals. Results: Nine articles were identified including 129 individuals. Stem cell transplantation was an effective treatment for Parkinson's disease (WMD=-14.86; 95% CI: -16.62 to -13.10; P<0.00001), with neural stem cells, umbilical cord mesenchymal stem cells (UCMSCs), and bone marrow mesenchymal stem cells (BMMSCs) being effective cell sources for transplantation. Stem cell transplantation can be effective for at least 12 months, but its long-term effectiveness remains unknown due to the limited studies monitoring patients for more than one year, not to mention decades. Conclusion: Data from controlled trials suggest that stem cell transplantation as a therapy for Parkinson's disease can be effective for at least 12 months. The factors that may influence its curative effect are time after transplantation and stem cell types.